ANALISIS PENDAPATAN USAHATANI PADI DI DESA CAMBA-CAMBA KECAMATAN BATANG KABUPATEN JENEPONTO - NUR ISMI; MARHAWATI; MUSTARI; MUHAMMAD IHSAN; SAMSYU RIJAL (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to determine the income and feasibility of rice farming in Camba-Camba Village, Batang District, Jeneponto Regency. In this study using quantitative descriptive research. The population in this study were 300 people and the number of respondents in this study was 10 percent or equal to 30 people. The sampling technique used is Simple Random Sampling. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques used are income analysis techniques, R / C ratio analysis, and Break Even Point (BEP) analysis. The results of this study indicate that the average income of rice farming in Camba-Camba Village, Batang District, Jeneponto Regency in one harvest season is IDR 19,104,717, the R / C ratio obtained is 3.4, which means that the farming experiences a profit. Thus, rice farming carried out by farmers in Camba-Camba Village, Batang District, Jeneponto Regency is feasible to be cultivated by farmers.